P505 Real word long-term efficacy and safety of vedolizumab in managing ulcerative colitis versus crohn's disease: results from "long vedo" italian multicenter study. (30th January 2023) - Mocci, G; Maconi, G; Onidi, F M; Cataletti, G; Elisei, W; Scaldaferri, F; Lorenzetti, R; Pagnini, C; Scarcelli, A; Graziani, M G; Di Paolo, M C; Pranzo, G; et al.
Abstract: Background: Current data about long-term use of vedolizumab (VDZ) in ulcerative colitis (UC) versus Crohn's disease (CD) patients are limited. We aimed to assess whether there are differences in term of long-term efficacy and safety of VDZ in UC vs. CD patients. Methods: Clinical activity was scored according to the Mayo score in UC and to the Harvey-Bradshaw Index (HBI) in CD. The primary endpoints were the achievement of clinical remission within 6 month of treatment, maintenance of clinical remission during a long follow-up, and safety. Secondary endpoints were clinical response to treatment, achievement of mucosal healing (MH), steroid discontinuation, and treatment optimization during the follow-up. Results: The study group consisted of 729 patients (475 patients with UC and 254 CD patients with CD) with a median follow-up of 18 (interquartile range 6-36) months. Clinical remission at the 6 th month of treatment was achieved in 488 (66.9%) patients, higher in CD patients (74.4 vs. 62.9, p<0.000) while, at the maximal follow-up, it was achieved and maintained in 81.5% of patients (UC vs. CD, p=0.667). At uni- and multivariate analysis, reaching clinical remission at the 6 th month of treatment (p=0.001) and being naïve to biologics were significantly associated with longer clinical remission (p<0.0001). Long-term follow up clinical response was significantly higher in UC vs. CD (p=0.023) and surgery occurred more frequently in CD (p=0.04), while no difference were found between UC and CD about the other secondary endpoints Conclusion: Overall, no significant differences were found about the long-term use of VDZ in UC vs. CD. However, we identified some parameters the can help the physician to predict the long-term efficacy of this drug.